Επίδρασης των φρέσκων υπολειμμάτων φυτοπροστατευτικών προιόντων στη βιωσιμότητα του αρπακτικού εντόμου Nesidiocoris tenuis. - Βίκτωρος, Ειρήνη (Department of Agricultural Sciences,Biotechnology and Food Sciences,Cyprus University of Technology, 2013)
Nesidiocoris tenuis (Hemiptera: Miridae) is one of the natural enemies commonly encountered in tomato crops. The last few years the use of pesticides has rapidly increased in an effort suppress diseases and pests of tomato crops, as a result there were consequences on the environment and on the health of consumers and farmers. Furthermore, the continuous use of pesticides and other chemical substances in agriculture has brought about a series of chain reaction effects on insects that are considered valuable to farming. The aim of this project was to assess the effects of pesticide residues from the following plant protection products: thiacloprid, spinosad, emamectin benzoate, metaflumizone, chlorantraniliprole, indoxacarb and copper hydroxide on the viability fifth instar nymphs of the zoophytophagous predator Nesidiocoris tenuis. The results of this project revealed that indoxacarb, chlorantraniliprole, copper hydroxide, metaflumizone and emamectin benzoate were responsible for less than 25% mortality of N. tenuis. According to the International Biological Control Organization these substances can be classified as “harmless” and as a result they can be applied during integrated pest management programmes. Thiacloprid and spinosad caused 28% and 27% mortality respectively which classifies them as “slightly harmful” according to IOBC. Nevertheless, it is advisable that their use is restricted and maintained to a minimum; especially since they were proven to be a lot more toxic that the rest of the products tested during this project. Published studies by other researchers have also indicated the need for further research as there is insufficient information regarding N. tenuis.
Keywords: Nesidiocoris tenuis; Thiacloprid; Spinosad